Long-term antiviral efficacy of entecavir and liver histology improvement in Chinese patients with hepatitis B virus-related cirrhosis - Xu, Yan (World journal of gastroenterology : WJG, 2015)
To evaluate the clinical outcomes of 240-wk treatment with entecavir (0.5 mg) in Chinese nucleoside-naive patients with cirrhosis. A total of 204 nucleoside-naive patients with compensated (n = 96) or decompensated (n = 108) hepatitis B virus (HBV)-induced cirrhosis at the Department of Gastroenterology of the China-Japan Union Hospital (Jilin University, Changchun, China) who were treated with entecavir (0.5 mg) for 240 wk were enrolled in this study. Liver biopsy samples obtained from 38 patients prior to treatment (baseline) and at week 240 were evaluated by different independent histopathologists. Efficacy assessments included the proportions of patients who achieved an HBV DNA level < 500 copies/mL, the association of interleukin-28B genetic variation with antivirus therapy, clinical outcomes, and histologic improvement. Changes in liver disease severity were analyzed, and liver histologic evaluation was performed in 38 patients with paired biopsies. Student t tests were used to compare the means of continuous variables between the groups, and the proportions of patients who achieved the endpoints were compared using the χ(2) test. At week 240, 87.5% of the patients with compensated cirrhosis and 92.6% of the patients with decompensated cirrhosis achieved a HBV DNA level < 500 copies/mL. Three patients had genotypic entecavir resistance within the 240-wk period. No significant association was observed between virologic response and interleukin-28 genotype (CT, 88.2% vs CC, 90.6%). The proportion of patients with Child-Pugh class A disease was significantly increased at week 240 (68%) from the baseline (47%; P < 0.01). The proportion of patients with Child-Pugh class B disease was significantly decreased at week 240 (25%) from the baseline (39%; P = 0.02). In the patients with paired liver biopsies, the mean reduction in the Knodell necroinflammatory score from the baseline was 3.58 ± 1.03 points (7.11 ± 1.80 vs 3.53 ± 1.35, P < 0.01). The mean reduction in Ishak fibrosis score from the baseline was 1.26 ± 0.64 points (5.58 ± 0.50 vs 4.32 ± 0.81, P < 0.01). Entecavir is an effective treatment option for patients with HBV-related compensated or decompensated cirrhosis that can result in sustained virologic suppression and histologic improvement.